Benthic foraminiferal paleoecology and depositional patterns during the Albian at DSDP Site 327 (Falkland Plateau). (October 2017) - Lopes, Fernando M.; Koutsoukos, Eduardo A.M.; Kochhann, Karlos G.D.; Savian, Jairo F.; Fauth, Gerson
Abstract: The present paleoenvironmental study uses a spectrum of analytical methods, such as benthic foraminiferal assemblages, total organic carbon (TOC), calcium carbonate (CaCO3 ) contents and magnetic susceptibility (MS), to monitor variations in primary productivity, bottom-water oxygenation and depositional patterns within the Albian interval recovered at DSDP Site 327, Hole A, Falkland Plateau. Thirty-three benthic foraminiferal species were identified in the studied section and, based on the abundances of morphogroups (epifaunal and shallow infaunal), two distinct associations were identified. Stratigraphic intervals dominated by the epifaunal morphogroup can be interpreted as indicative of bottom-waters with low-oxygen content. However, these decreases in oxygenation were not vigorous enough to establish a dominance of deep-infaunal morphotypes, as supported by the low TOC values. Intervals dominated by the shallow infaunal morphogroup were interpreted as subjected to moderate to high nutrient flux to the ocean floor. These intervals are associated with high MS values and low CaCO3 content, suggesting that dissolution processes, rather than increased primary productivity, controlled CaCO3 accumulation in the studied section. Furthermore, faunal analysis points to deposition in an outer neritic to upper bathyal paleoenvironment. Highlights: We realize a paleoecological study using different tools in the Albian. We identified stratigraphic levels with low-oxygen content and high productivity. Foraminiferal assemblage and sedimentologic parameters shows dissolution of CaCO3 .